2013
DOI: 10.5588/ijtld.13.0032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human immunodeficiency virus and CD4 count on tuberculosis diagnosis: analysis of city-wide data from Cape Town, South Africa

Abstract: Background The impact of HIV-infection and CD4 count on diagnosis of tuberculosis (TB) at a population level is incompletely defined. Objective To determine how HIV-infection and CD4 count affect disease site, sputum smear status and overall rate of laboratory confirmation (sputum smear microscopy or culture) of TB cases under routine programme conditions. Design Retrospective analysis of the 2009 electronic TB register for Cape Town, South Africa. Results Of 29,478 TB cases notified in 2009, HIV-status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 23 publications
4
46
0
4
Order By: Relevance
“…Th ere are reports that the prevalence of HIV/TB coinfection is higher in intravenous drug users (IVDUs) [15]. In our study, the prevalence of viral hepatitis infection in patients who died from TB was 40%, which is typical of populations where IVDU is the main HIV transmission route [23], but as it was also high in patients who died from other diseases -this only shows that IVDU is common among the Latvian HIV/AIDS population.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Th ere are reports that the prevalence of HIV/TB coinfection is higher in intravenous drug users (IVDUs) [15]. In our study, the prevalence of viral hepatitis infection in patients who died from TB was 40%, which is typical of populations where IVDU is the main HIV transmission route [23], but as it was also high in patients who died from other diseases -this only shows that IVDU is common among the Latvian HIV/AIDS population.…”
Section: Discussionmentioning
confidence: 82%
“…In the EU on average, this rate was 4.6% [5]. In advanced stages of HIV course, cavitary TB is uncommon and lower-lobe infi ltrates or miliary dissemination as well as extrapulmonary TB usually occurs [6,15]. If extrapulmonary TB develops in immunocompetent individuals, no active pulmonary lesions are usually found at that time; however, in HIV/AIDS patients disseminated TB is characterized by simultaneous involvement of the lungs and other organs [16,30].…”
Section: Introductionmentioning
confidence: 99%
“…11 Another South African population based study found 61% of patients with TB had CD4 count of <200/µl similar to this study. 12 There are several limitations in this study. First, author had a small sample size hence the results cannot be generalized to population so there is a need for larger studies to confirm the findings.…”
Section: Resultsmentioning
confidence: 99%
“…In patients in lower CD4 strata, the diagnostic challenges are substantial because of a high proportion of smear-negative, extrapulmonary and disseminated tuberculosis. 7 In four randomised controlled studies, commencing ART earlier for patients with low CD4 T-cell counts (2 weeks for patients with fewer than 50 CD4 cells per mm 3 , otherwise within 4-12 weeks of treatment for tuberculosis) was associated with a survival benefit . 8 During advanced immunosuppression, initiation of ART in patients coinfected with HIV and tuberculosis can lead to both unmasking of tuberculosis in those with previously undiagnosed disease or a paradoxical immune reconstitution inflammatory syndrome (IRIS).…”
Section: Introductionmentioning
confidence: 99%